Neurochemical correlates of functional decline in amyotrophic lateral sclerosis. Issue 3 (22nd November 2018) - Cheong, Ian; Deelchand, Dinesh K; Eberly, Lynn E; Marjańska, Małgorzata; Manousakis, Georgios; Guliani, Gaurav; Walk, David; Öz, Gülin
Abstract : Objective: To determine whether proton magnetic resonance spectroscopy ( 1 H-MRS) can detect neurochemical changes in amyotrophic lateral sclerosis (ALS) associated with heterogeneous functional decline. Methods: Nineteen participants with early-stage ALS and 18 age-matched and sex ratio-matched controls underwent ultra-high field 1 H-MRS scans of the upper limb motor cortex and pons, ALS Functional Rating Scale-Revised (ALSFRS-R total, upper limb and bulbar) and upper motor neuron burden assessments in a longitudinal observational study design with follow-up assessments at 6 and 12 months. Slopes of neurochemical levels over time were compared between patient subgroups classified by the rate of upper limb or bulbar functional decline. 1 H-MRS and clinical ratings at baseline were assessed for ability to predict study withdrawal due to disease progression. Results: Motor cortex total N -acetylaspartate to myo -inositol ratio (tNAA:mIns) significantly declined in patients who worsened in upper limb function over the follow-up period (n=9, p=0.002). Pons glutamate + glutamine significantly increased in patients who worsened in bulbar function (n=6, p<0.0001). Neurochemical levels did not change in patients with stable function (n=5–6) or in healthy controls (n=14–16) over time. Motor cortex tNAA:mIns and ALSFRS-R at baseline were significantly lower in patients who withdrew from follow-up due to disease progression (n=6) compared with patients who completed the 12-month scan (n=10) (p<0.001 for tNAA:mIns; p<0.01 for ALSFRS-R), with a substantially larger overlap in ALSFRS-R between groups. Conclusion: Neurochemical changes in motor areas of the brain are associated with functional decline in corresponding body regions. 1 H-MRS was a better predictor of study withdrawal due to ALS progression than ALSFRS-R.